Politeness Strategies Used in Directive Speech Acts in Classroom Interaction (LINGUISTIK TERAPAN, 2015)
This research deals with politeness strategies used in directive speech acts in classroom interaction. It specially focused on types of politeness strategies which were used by teachers and students in directive speech acts, how and why those types were realized the way they were. The approach used in this research was based on politeness theory proposed by Brown and Levinson (1987). The data were the transcriptions of the recorded observation and interview taken by using audio visual recorder in the classroom interaction of SMAN 1 Talawi, Batu Bara. The findings showed that all types of politeness strategies were applied in directive speech acts in classroom interaction. However, they were not used by all participants. Off record was not used in student to student interaction. The most dominant type of politeness strategies used was bald on record. It was used because of the limited vocabulary of the students when they speak English, because of efficiency, to avoid the misinterpretation on the participants, to show the teacher™s power when they commanded the students to do something and to show their firmness when they forbad or admonished the students not to do something. Keywords: Directive Speech Acts; Classroom Interaction; Politeness Strategies